2015
DOI: 10.1002/pd.4483
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk after noninvasive prenatal screening on cell‐free DNA circulating in maternal blood: does a new indication for invasive prenatal diagnosis require new criteria for confirmatory cytogenetic analysis?

Abstract: uncultured amniocytes for the targeted chromosome combined with a standard karyotype analysis can also be taken into consideration. 16 In conclusion, on the basis of our cytogenetic experience, the new indication for invasive prenatal diagnosis 'increased risk after NIPS on cell-free DNA circulating in maternal blood' requires new specific criteria for confirmatory cytogenetic analysis on amniocytes, and the appropriate communication by clinicians of the specific risk allows the application of appropriate labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This is because CVS has an increased risk for fetal loss compared with amniocentesis [ 30 , 31 ]. Furthermore, amniocentesis is preferable over CVS to avoid duplicating the original placental mosaicism that resulted in primary NIPT screening result: both CVS and NIPT may be then misleading when there is confined placental mosaicism [ 32 ]. The extent to which obstetric professionals and pregnant women are aware of the increased risk of CVS as an earlier diagnostic test (to complement the earlier NIPT test) in comparison to amniocentesis is not known, and the extent to which this increased risk would influence obstetric professionals’ or women’s preferences for the type of screening test, subsequent diagnostic test, or timing of these test needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…This is because CVS has an increased risk for fetal loss compared with amniocentesis [ 30 , 31 ]. Furthermore, amniocentesis is preferable over CVS to avoid duplicating the original placental mosaicism that resulted in primary NIPT screening result: both CVS and NIPT may be then misleading when there is confined placental mosaicism [ 32 ]. The extent to which obstetric professionals and pregnant women are aware of the increased risk of CVS as an earlier diagnostic test (to complement the earlier NIPT test) in comparison to amniocentesis is not known, and the extent to which this increased risk would influence obstetric professionals’ or women’s preferences for the type of screening test, subsequent diagnostic test, or timing of these test needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…Last, if serum were to be collected between 11 and 12 weeks' gestation, by the time the cf DNA test result is returned at 12 to 14 weeks' gestation, many pregnancies will be past the window in which CVS can be performed. However, some groups are recommending that confirmation of a cf DNA positive be confirmed by amniocentesis, because of the potential for confined placental mosaicism …”
Section: Discussionmentioning
confidence: 99%
“…However, some groups are recommending that confirmation of a cf DNA positive be confirmed by amniocentesis, because of the potential for confined placental mosaicism. 45 This serum-only approach could be considered in clinical settings where reliable NT measurements and a comprehensive first trimester ultrasound study are not readily available. Many studies have shown that NT is perhaps the best single marker for Down syndrome, but a comprehensive first trimester ultrasound study can also identify other important finding (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, only 3.5 % (1/29) trisomy 13 and 13.3 % (2/15) trisomy 18 cases were subsequently confirmed by chromosome analysis on amniotic fluid. The authors suggest that cytogenetic guidelines be changed to include a mandatory extended cytogenetic analysis to look for possible true fetal mosaicism in amniocytes when the indication is follow-up to a positive trisomy 21 or monosomy X NIPS, and a recommended extended analysis for trisomies 13 or 18 [53]. While these data and recommendations are interesting and merit further discussion, postnatal follow-up studies on fetuses with normal prenatal chromosome analysis and positive NIPS results would be more useful in informing the decision of whether or not to extend chromosome analysis.…”
Section: Discussionmentioning
confidence: 98%